Outcomes of remotely delivered behavioral insomnia interventions for children and adolescents: systematic review of randomized controlled trials - Lah, Suncica; Cao, Thanh Vinh (Frontiers in Sleep, 2024)
Paediatric insomnia is common and can be effectively treated with behavioural therapies delivered face-to face. Such treatments could also improve children's mood, cognition, and quality of life, and caregivers' well-being. There is a discrepancy between high needs and limited access to paediatric behavioural insomnia treatments, which could be improved by provision of technology enhanced interventions. No study reviewed outcomes of randomised controlled trials (RCTs) of remotely delivered psychological treatments for paediatric insomnia. The current study aimed to examine (i) the outcomes of RCTs for paediatric insomnia/insomnia symptoms and (ii) whether gains made in treatment extend to functional correlates. We conducted a systematic review according to Cochrane and PRISMA guidelines. PsychINFO, PubMed/Medline and Cochrane CENTRAL databases were searched for RCTs reporting on remotely delivered behavioural treatments for insomnia and insomnia symptoms. Data was abstracted and the risk of bias was assessed in November 2022 and November 2023. Seven RCTs (9 manuscripts) involving 786 participants, with the mean age from 19.3 months to 16.9 years, were identified. Four different treatments were used. Risk of bias ranged from low to high and was the highest for the randomisation process. Across studies, significant improvements were found in some (but not all) sleep parameters, namely: sleep quality and sleep efficacy on questionnaires and on actigraphy, despite heterogeneity of the treatments used, age of participants and instruments employed to validate outcomes. Improvements gained in treatments delivered remotely was compared to treatments delivered face-to-face in 3 studies and were found to be comparable or slightly lower. No worsening was observed on either objective or subjective measures of sleep, except for sleep onset latency and wake after sleep onset that improved on questionnaires but worsened on actigraphy in one study each. Children's mood improved across studies on parent and self-report measures. Other possible functional gains were understudied. Our study provides preliminary evidence of improved sleep following remotely delivered behavioural2 treatments for paediatric insomnia, and improvements in children's mood. Further research is needed to develop individualized treatments that will cater for different developmental needs and types of insomnia symptoms and examine not only group but also individual outcomes.